Poison Pills e gerenciamento de resultados: um estudo das Companhias Listadas na B3 - Azevedo, Yuri Gomes Paiva (Brasil, 2018)
This study aims to investigate if the poison pills influences on the earnings management level of the companies listed in B3. For this, data were collected regarding the presence of this antitakeover device as well as of “eternity” accessory clauses associated with the poison pills in the bylaws of 225 non-financial companies. The informations that are necessary to estimate the accruals discretionary by the model proposed by Dechow, Sloan and Sweeney (1995), as well as the control variables inserted in the econometric model, were obtained through the Bloomberg® database, comprising the period 2010-2016. Based on the results, it was verified that the the adoption of the poison pills doesn’t have a significant influence on the earnings management level. However, the non-existence of this relationship doesn’t indicate that these companies are not involved in earnings management practices, since the Poisonpill dummy is not statistically distinct from the base group, which is composed by companies that do not adopt poison pills and that present negative and significant relation with the discretionary accruals. Finally, in the national context, evidence has been found that "eternity" clauses can be inserted into the bylaws to exacerbate the level of earnings management, since the findings demonstrate that poison pills with "etenity" clauses effectively differentiate themselves of the poison pills, presenting a positive and statistically significant relation with discretionary accruals.
Keywords: Poison Pills; Gerenciamento de resultados; Dispositivos Anti-Takeover; CNPQ::CIENCIAS SOCIAIS APLICADAS: CIÊNCIAS CONTÁBEIS